Gnostički autor Harolda Blooma - Šimić, Krešimir; Stubičar, Robert (Anafora, 2024)
The article contextualizes at first the occurrence of the so-called authorship studies that arose as a kind of reaction to the post-structuralist (R. Barthes and M. Foucault) redefinition of authorship. Harold Bloom then positioned himself in this context. Namely, from the belief that post-structuralist anti-humanist tendencies initiated degenerative processes, and ultimately the disintegration of literature, he placed the canon and the author at the forefront of his literary theory. While much has been written about the first term, the second—the question of the authorship—has been mostly neglected in Bloom studies. Therefore, the article focuses primarily on Bloom’s interpretation of the author. The article tries to show that his understanding of authorship (as well as the canon, after all) derives from the Gnostic tradition (Valentin and Luria). For Bloom, the author is, it is concluded, primarily a genius—one who creates inspired by a “spark,” a pneuma, a divinity at the bottom of one’s own mind, which is actually also a certain form of anti-humanism.